Use of diet supplements in older patients - Prylińska, Monika; Bieniek, Daria; Karpińska, Anna; Skierkowska, Natalia; Androsiuk-Perkowska, Joanna; Perkowski, Radosław; Husejko, Jakub; Topka, Weronika; Gajos, Małgorzata; Kujawska, Agnieszka; et al. (Journal of Education, Health and Sport, 2018)
Introduction: Dietary supplements are ingredients in the diet of a growing number of people, especially seniors. The physiological processes of aging of the body are often accompanied by disease processes, which may result in malnutrition of the body and supplement using could be a presumably auxiliary therapy. Material and Methods: The paper reviews literature using the EBSCO and Google Scholar databases. Articles have been analyzed using the keywords aging, elderly, malnutrition, supplements, vitamins, minerals, supplementation. The article presents effects of the use of individual dietary supplements. Results: Among the elderly, it would be worth to consider supplementation with vitamins D3, K2, B12. In addition to vitamins, iron, selenium, creatine, leucine, milk thistle, omega 3 acids use could be considered. Conclusions: Vitamins, microelements and amino acids are essential for the proper functioning of the body, while some groups of elderly are malnutritioned and could gain benefit from diet supplements. Individually prescribed therapy using supplements should be based on deficiencies examination using objective tests, for example blood test.